1987
DOI: 10.1111/j.1600-0404.1987.tb07888.x
|View full text |Cite
|
Sign up to set email alerts
|

Management of urinary incontinence in children with myelomeningocele

Abstract: Several forms of treatment of lower urinary tract functional disorders have been attempted in children with myelomeningocele (MMC). Intravesical electrical stimulation was attempted in 10 patients. Urinary control was achieved in one and in the remaining 9 either the bladder was resistant to stimulation or the children discontinued the treatment due to loss of interest. A combined anticholinergic and calcium blocking agent, terodiline, was tested in 8: symptoms improved in 4, but bladder compliance was unchang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…However, our results show that urinary control for two to three hours is perceived as con-siderably more stressful to the child than urinary control for three hours or more. In accordance with other authors (Bille et al 1984, Petersen 1987, we therefore consider that social continence is the ability to stay dry for three hours or more during the day. By using CIC more frequently, social continence may be achieved among a larger proportion of children with myelomeningocele (Cass et al.…”
Section: Discussionsupporting
confidence: 57%
“…However, our results show that urinary control for two to three hours is perceived as con-siderably more stressful to the child than urinary control for three hours or more. In accordance with other authors (Bille et al 1984, Petersen 1987, we therefore consider that social continence is the ability to stay dry for three hours or more during the day. By using CIC more frequently, social continence may be achieved among a larger proportion of children with myelomeningocele (Cass et al.…”
Section: Discussionsupporting
confidence: 57%
“…After removing 16 duplicates, we screened the titles and abstracts of 193 references. Eleven studies were analyzed in full text, and five were excluded: four were not RCTs, [16][17][18][19] and one study included participants with another neurological dysfunction (RBR-4qjdxq). In addition, two studies were classified as "awaiting classification" due to not having been found in full text.…”
Section: Results Of the Searchmentioning
confidence: 99%